Entrepreneurial Motivation Competence and Growth of Micro and Small Enterprise in Nairobi County - Thaimuta, Justus; Ngugi, Patrick; Nyang'au, Samson (European Journal of Business and Strategic Management, 2024)
Purpose: The purpose of the study was to establish how entrepreneurial motivation competence influences the growth of micro and small enterprise in Nairobi County. Micro and Small Enterprises (MSEs) are important drivers of economic growth and development in Kenya. These enterprises create employment, facilitate wealth creation and form the backbone for private sector growth and expansion. The numerous challenges facing MSEs in Kenya are both internal and external to their operations. Many businesses are characterized by entrepreneurs' lack of proper entrepreneurial training, lack of marketing capacity and broad operational capacity, lack of business innovation, inadequate business training, lack of motivation for business and pro-activeness. Methodology: The study adopted a descriptive survey design. There were 1,236,907 operating businesses categorized as MSEs in Nairobi County by the year 2020. To select the MSE in all the regions in Nairobi County, cluster sampling techniques was employed, first to identify the various MSEs and clusters relevant to this study. Seventeen clusters were identified according to where they are located. 384 respondents formed the study sample. The selection of the sample from each cluster of the study was through simple random sampling. The study used a questionnaire to collect primary data, which was then analyzed using Statistical Package for Social Sciences (SPSS version 23). Data analysis was done using descriptive statistics, Pearson correlation coefficient and regression analysis. Findings: The findings showed that an increase in Innovation competence would result to increase in growth of micro and small enterprise in Nairobi County. The findings showed that a unit increase in Entrepreneurial Motivation competence would result to an increase of 0.639 units in growth of micro and small enterprise in Nairobi County. The univariate analysis fitted to test the relationship between motivation competence and growth of micro and small enterprises in Nairobi County show that entrepreneurial motivation competence explained 29.9% of the variation in growth of micro and small enterprises in Nairobi County other factors held constant. Unique Contribution to Theory, Practice and Policy: The Theory that underpinned the study was entrepreneurial competency theory. This study recommended that micro and small enterprises should have a strong mission and vision that is shared with all employees. This will help to create a shared sense of purpose and ensure that everyone is working towards the same goal. Investing in training and development will help to increase employee motivation.